Crew injuries in container vessel accidents. Issue 5 (3rd July 2016) - Zheng, Yishu; Talley, Wayne K.; Jin, Di; Ng, ManWo
ABSTRACT: This paper investigates determinants of the probability of non-fatal and fatal crew injuries in container vessel accidents. The determinants are deduced from an estimated probit regression equation based upon 2001–2008 U.S. Coast Guard container vessel accident data. The estimation results suggest that a crew member is: (1) less likely to have a non-fatal injury in containership and ro-ro container vessel accidents if the vessel has a steel hull and the vessel accident occurs at nighttime, (2) more likely to have a fatal injury if fire is involved in containership and ro-ro container vessel accidents, and (3) less likely to have a fatal injury in containership and ro-ro container vessel accidents if the vessel is U.S. flagged, steel hulled, and powered by a diesel engine. These results are critical in developing new policies in reducing non-fatal and fatal crew injuries in container vessel accidents.